Estresse e ansiedade percebidos por pais de crianças com câncer - Oliveira, Kayna Moraes de [UNIFESP] (2016)
Introduction: the diagnosis and treatment of cancer in children and adolescents cause symptoms of anxiety and stress on parents, affecting the well-being of the whole family. In this way the care of the family is essential and must be conducted based on the principles of Patient and Family Centered Care. We questioned the perceptions of stress and anxiety in the perspective of parents of children/adolescents with cancer; and the relationship of sociodemograpic characteristics and the occurrence of perceived stress and anxiety. Objective: To evaluate the perceptions of stress and anxiety from the perspective of parents of children and adolescents with cancer. Method: A survey was conducted in a reference institute of pediatric oncology, in Sao Paulo, linked to a federal university. The study was approved by the ethics committee and the participants signed the consent form. Data were obtained by filling out a form with information about the parent?s social demographic data and the characteristics of the children/ adolescents with cancer; and application of two measuring instruments The State-Trait Anxiety Inventory (scales STAI-S e T) and Pediatric Inventory for Parents - PIP, with two sub-scales: frequency (PIP-F) and difficulty (PIP-D), both validated for the Brazilian Portuguese language. Data analysis was performed descriptively, inferential (p<0.05) and by non-parametric tests. Results: the sample consisted of 89 parents of children/adolescents with cancer. The final scores of the PIP-F ranged from 84-186 with average of 138; and PIP-D ranged from 77-180 with average of 122. On PIP-F, the older the parents, the lower was the scores of perceived stress on medical care domain (p=0.0292). As to the PIP-D, in the communication domain, parents older than 51 years had higher average scores of stress (p=0.0365); and parents with a higher level of education showed lower scores (p=0.0181). Parents with less time of study pointed higher scores of stress in medical care domain in PIP-D (p=0.0130); the average perceived of parental anxiety scores were higher in STAI-T compared to STAI-S. There was a correlation between the scores of the STAI scales, showing that the higher the anxiety state, the higher the trait of anxiety of the father/mother (p<0.0001). Parents of female children/adolescents have higher perceptions of anxiety state (p=0.0015) and trait (p=0,0464) than parents of male children/adolescents. Parents who responded to the questions in the hospitalization had higher perceptions of anxiety in the STAI-T (p=0.0196). The higher the stress perceived by parents, the higher the anxiety in STAI-S and STAI-T. Conclusion: the perception of parental stress presented variations in both subscales, with the highest average in the PIP-F than PIP-D. Parents with less study had higher perceived stress scores in most areas of the subscales; and older parents had higher scores in the frequency of perceived stress concerning medical care. On the subject of anxiety, parents had higher average scores of anxiety trait than state; the scores of perception of anxiety were higher in parents of female children/adolescents; and during hospitalization period. There was significant correlation between the scores of stress and anxiety